What Not to Do If You Turn Invisible - Ross Welford (London : Harper Collins Children's Books, 2017)
Turning invisible at will: it's one way of curing your acne. But far more drastic than 13 year-old Ethel Leatherhead intended when she tried a combination of untested medicines and a sunbed. It's fun at first, being invisible. And aided by her friend Boydy, she manages to keep her extraordinary ability secret. Or does she...? When one day the invisibility fails to wear off, Ethel is thrown into a nightmare of lies and deception as she struggles to keep herself safe, to find the remedy that will make her seen again - and solve the mystery of her own birth.